THE PEDAGOGICAL PRACTICE WITH AUTISM STUDENTS IN CHILDREN EDUCATION - Estácio Neto, Francisco; Barcelos Corrêa, Jackeline; Eduarda das Graças Gomes de Souza, Maria (LINKSCIENCEPLACE, 2026)
Autism Spectrum Disorder (ASD) is a developmental neurological disorder that begins early in childhood and lasts for a person's entire life. It affects how a person acts and interacts with others, communicates and learns. It includes what used to be known as Asperger's syndrome and invasive developmental disorders. During the early years of childhood, children are growing and developing at an incredible rate, and this is the ideal time for the child to learn how to connect with others, regulate their senses, improve communication and practice many other skills. In this context, this work intends to discuss the pedagogical practices related to the teaching of autistic children in Early Childhood Education. Thus, the research developed qualitatively and quantitatively through a theoretical contribution and a research carried out with teachers from the public and private schools of the city of Porciúncula / RJ. It has been shown that the best practice approach when looking at the most important skills for Early Childhood teachers working with children with ASD are communication and social skills. In addition, it has been noted that providing early intervention for autistic children can contribute to the success rate in school, and for that, it is the responsibility of all teachers and principals to seek more educational training, workshops, and best practice approach to autistic children, and for this, the Public Power must be engaged in this process.